RANCANG BANGUN PROTOTYPE PINTU AIR IRIGASI OTOMATIS PENCEGAH KEBAKARAN LAHAN GAMBUT MENGGUNAKAN MIKROKONTROLER - Ahmad Ryan Nur Rahman (Fakultas MIPA Universitas Lambung Mangkurat, 2021)
Forest and land fires always occur every year in Indonesia. Data from the Ministry of Environment and Forestry of the Republic of Indonesia recorded that from January to September 2019, a total of 227,304 ha of fires occurred for peatlands, and peat fires in Borneo with a burned area of 135,991 ha have the biggest impacts in Indonesia, which would increase every year if not handled well. Peatlands that experience drought are one of the reasons why they burn easily. One of the efforts made by the Indonesian government to prevent land fires is by making irrigation gates that function to wet the land (Rewetting), because in normal condition peatlands have to be submerged in water. In this study, a prototype design of an irrigation sluice gate with automatic control using a microcontroller were developed which works by detecting the condition of the peatland ecosystem using sensors of soil moisture and air temperature. The irrigation water gate prototype can move wide open, moderately open, and closed, according to the state of the peatland ecosystem, namely: when it is dry, wet, and the peatland is submerged.